2020
DOI: 10.15421/2020_251
|View full text |Cite
|
Sign up to set email alerts
|

The level of adaptability of perspective samples of soft and durum spring wheat in Ukrainian forest-steppe

Abstract: In the Eastern Forest-Steppe zone of Ukraine, which is characterized by a sharp change in weather conditions during the growing season of agricultural crops, it is very important to grow hybrids that are most adapted to frequent weather anomalies during the growing season. This can significantly reduce their negative impact on the productivity of spring wheat. The results of a study of 20 samples (soft spring wheat Triticum aestivum L.) and (durum spring wheat Triticum durum) of different ecological and geogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The research of Yu.Yu. Chuprina et al [28] found that the duration of the interphase period "sowing-seedling" of winter wheat was more influenced by the amount of precipitation, but the scientists did not take into account the moisture of the seed layer of the soil, which is a more important indicator. It was determined that, on average, over the years of research, the interphase period of BBCH 00-09 lasted from 13 to 14 days at a moisture content of the seed layer of the soil of 22.2-22.4 mm, while it lasted 11 days at a moisture content of 46.8 mm.…”
Section: Table 4 Continuedmentioning
confidence: 99%
“…The research of Yu.Yu. Chuprina et al [28] found that the duration of the interphase period "sowing-seedling" of winter wheat was more influenced by the amount of precipitation, but the scientists did not take into account the moisture of the seed layer of the soil, which is a more important indicator. It was determined that, on average, over the years of research, the interphase period of BBCH 00-09 lasted from 13 to 14 days at a moisture content of the seed layer of the soil of 22.2-22.4 mm, while it lasted 11 days at a moisture content of 46.8 mm.…”
Section: Table 4 Continuedmentioning
confidence: 99%
“…The yield of winter wheat depends on many factors, including meteorological conditions and the application of plant growth regulators. Meteorological conditions, such as temperature, precipitation, lighting and humidity, can significantly affect the development of wheat and its yield [3]. Growth regulators can also have a positive effect on wheat yield.…”
Section: Introductionmentioning
confidence: 99%
“…They can provide an optimal combination of nutrients and stimulating substances for the growth and development of plants. Growth regulators, such as potassium humate or sodium humate, can improve the development of the root system of plants, provide better assimilation of nutrients and water, and also increase the resistance of plants to stressful conditions [3,4]. Combining nitrogen fertilizers with growth regulators can contribute to an even greater improvement in the yield of winter wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Високий потенціал родючості чорноземних ґрунтів створює сприятливі умови для вирощування олійних культур, зокрема і соняшника. Але потужний насіннєвий банк сегетальної рослинності спричиняє негативний вплив на рослини соняшника, у той час коли значна частина елементів живлення у ґрунті міститься в формі складних органічних або нерозчинних мінеральних сполук і тому не може засвоюватися корінням рослин [1]. Тоді як використання різних способів основного обробітку ґрунту впливають на його фітосанітарний стан, вологість, інтенсивність діяльності мікроорганізмів, аерацію, регулює поживний режим, підвищуючи ефективність добрив і створює сприятливі умови для вирощування гібридів соняшника [4; 5; 7].Головним завданням основного обробітку ґрунту під соняшник є контроль за фітосанітарним станом посівів, а саме максимальне знищення багаторічних та однорічних бур'янів, накопичення і збереження якомога більшої кількості вологи у кореневмісному шарі після осінньо-зимових і ранньовесняних опадів, мобілізація поживних речовин, активізація біологічних процесів ґрунту, створення оптимальної структури орного шару, запобігання вітровій і водній ерозії [3].Безполицевий обробіток ґрунту зі залишенням на полі нетоварної частини урожаю у вигляді мульчі, що проводиться без перевертання скиби, суттєво впливає на перебіг і спрямованість ґрунтових процесів, зокрема, на азотний режим чорноземів.…”
unclassified
“…Високий потенціал родючості чорноземних ґрунтів створює сприятливі умови для вирощування олійних культур, зокрема і соняшника. Але потужний насіннєвий банк сегетальної рослинності спричиняє негативний вплив на рослини соняшника, у той час коли значна частина елементів живлення у ґрунті міститься в формі складних органічних або нерозчинних мінеральних сполук і тому не може засвоюватися корінням рослин [1]. Тоді як використання різних способів основного обробітку ґрунту впливають на його фітосанітарний стан, вологість, інтенсивність діяльності мікроорганізмів, аерацію, регулює поживний режим, підвищуючи ефективність добрив і створює сприятливі умови для вирощування гібридів соняшника [4; 5; 7].…”
unclassified